2021
DOI: 10.1002/tesq.3038
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English to Special Educational Need Students through an Online Tool

Abstract: Language learning through online tools has become customary, especially during COVID-19 pandemic, but this type of education does not always consider the requirements for students with special educational needs (SEN) despite teachers struggle to include disabled students in online teaching. This article presents the educational potential of using Universal Design for Learning (UDL) and Web Content Accessibility Guidelines (WCAG) to help SEN students learn English. First, a theoretical framework that covers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This situation offers many possibilities for renewing existing adaptations and modifications to improve the teaching and learning process of students with special needs in the context of effective teaching. In addition, Barros et al (2021) reported in their study that effective learning takes place after practical examples and practical application of some activities in the process of teaching foreign languages to students with special needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation offers many possibilities for renewing existing adaptations and modifications to improve the teaching and learning process of students with special needs in the context of effective teaching. In addition, Barros et al (2021) reported in their study that effective learning takes place after practical examples and practical application of some activities in the process of teaching foreign languages to students with special needs.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is essential to provide a language teaching process in which students with special needs are approached in a fair manner, adaptations are implemented according to individual learning speed, opportunities are specially created for them to participate in course activities, and a positive classroom environment is cultivated (Chen, 2022;Miller, 2016;Rapti et al, 2023). At this point, it becomes even more important for foreign language teachers to include the necessary adaptations to ensure effective teaching for students with special needs in the process of successful inclusion practices (Barros et al, 2021;Frumos, 2020;Handle, 2010;Rezabala et al, 2020). Otherwise, inclusion practices in language teaching to students with special needs will not be achieved, but rather, this might, most likely, lead to un/intentional segregation practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Internet+ boom, many educational contents must be connected to the Internet of Things and cloud computing. On the one hand, students are increasingly interested in the Internet (María et al et al, 2021). They use IoT and cloud computing to gain in-depth knowledge, interact with their teachers, and connect anytime, anywhere; on the other hand, vocal teachers change "Internet" into Education+Internet, which should put education in a dominant position and the Internet in a subordinate position, to make good use of IoT and cloud computing technology to improve the modern level of vocal Singing teaching level.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The development of technology makes university English teaching free from the limitations of space and time, which enables teachers to carry out teaching anytime and anywhere, and teachers can also introduce richer teaching content for students in the teaching process [8][9]. To a certain extent, this can exercise students' practical ability and further improve their comprehensive quality [10][11].…”
Section: Introductionmentioning
confidence: 99%